Zscaler cloud security essentials discover how to securely embrace cloud efficiency, intelligence, and agility with Zscaler - Devarasetty, Ravi (Packt Publishing, 2021)
Harness the capabilities of Zscaler to deliver a secure, cloud-based, scalable web proxy and provide a zero-trust network access solution for private enterprise application access to end users. Many organizations are moving away from on-premises solutions to simplify administration and reduce expensive hardware upgrades. This book uses real-world examples of deployments to help you explore Zscaler, an information security platform that offers cloud-based security for both web traffic and private enterprise applications.You'll start by understanding how Zscaler was born in the cloud, how it evolved into a mature product, and how it continues to do so with the addition of sophisticated features that are necessary to stay ahead in today's corporate environment. The book then covers Zscaler Internet Access and Zscaler Private Access architectures in detail, before moving on to show you how to map future security requirements to ZIA features and transition your business applications to ZPA. As you make progress, you'll get to grips with all the essential features needed to architect a customized security solution and support it. Finally, you'll find out how to troubleshoot the newly implemented ZIA and ZPA solutions and make them work efficiently for your enterprise.By the end of this Zscaler book, you'll have developed the skills to design, deploy, implement, and support a customized Zscaler security solution. This book is for security engineers, security architects, security managers, and security operations specialists who may be involved in transitioning to or from Zscaler or want to learn about deployment, implementation, and support of a Zscaler solution. Anyone looking to step into the ever-expanding world of zero-trust network access using the Zscaler solution will also find this book useful.